Forms of Change in Learning After the Implementation of the Merdeka Curriculum at MI Irsyadul Mubtadi'in - Maulida Mella Inayah; Triana Rosalina Noor (LP3M KH Yazid Karimullah Institute, 2025)
This study aims to describe the forms of learning transformation following the implementation of the Merdeka Curriculum at MI Irsyadul Mubtadi’in. The research employed a qualitative method with a case study approach through interviews, observations, and documentation. The results indicate significant changes in seven components of learning: learning objectives, teaching materials, methods, media, students, teachers, and evaluation. Learning objectives are now formulated as learning outcomes, while lesson plans (RPP) have been replaced with more detailed teaching modules. Teaching methods emphasize teacher collaboration and the use of more varied strategies. Learning media have undergone digitalization, encouraging more intensive use of technology. In terms of students, the development of interests, talents, and abilities has become the main focus. Teachers serve as facilitators and are also required to manage digital administration. Learning evaluation is carried out through formative and summative assessments, final assessments, as well as MBK and AKMI assessments, with the Pancasila Student Profile Strengthening Project (P5) serving as a substitute for practical exams. This study provides a comprehensive depiction of the implementation of the Merdeka Curriculum in classroom learning and its implications for the teaching and learning process in madrasah settings.